Dervishes in Croatia - Bagarić, Petar; Petrović, Željka; Rubić, Tihana (2008)
The paper is based on observation and narrative interviews, both particular anthropological fieldwork methods. The short-term ethnographic fieldwork was conducted among dervishes of the Rufai order, situated in Pehlin (improvised settlement, town of Rijeka, Adriatic Coast). The intention of the research was to gather deeper insights into the question of minorities as a whole, as well as the different aspects of social and religious life of minority groups in Croatia.
Projekt MZOS
ENG